Efektivitas Perlindungan Hukum terhadap Merek UMKM dalam Industri Kreatif: Studi Kasus Deswa Craft - Hasuri; Ayu Destika (CV Rewang Rencang, 2025)
This study discusses the challenges of trademark protection for SMEs, with a case study of Deswa Craft in Serang. Using a normative juridical approach and descriptive analytical method, it was found that the effectiveness of trademark protection is hindered by low legal literacy, high registration costs, and lack of assistance. However, IPR is a strategic asset in enhancing competitiveness. The government has digitized the system, but its implementation remains uneven. This research recommends improving legal education, simplifying registration procedures, and fostering cross-sector collaboration to ensure SMEs' inclusive and sustainable access to IPR protection.